Numerical analysis of the thermal and electrical performance of concentrated photovoltaic systems integrated with multiple phase change materials - Atef Chibani; Slimane Merouani; Riad Badji; Farhan Lafta Rashid; Mohamed Kezzar; Sahar Ahmed Idris; Mohamed Rafik Sari; B. Rushi Kumar; Sunitha Nagarathnam (Case Studies in Thermal Engineering)
Great attention has been paid to the improvement of the efficiency of photovoltaic (PV) systems and their profit due to the constantly growing demand for effective energy solutions. The rise of the demands for efficient energy solutions in terms of environmental influence needed much concern to make solar (PV) systems work better, especially in the hot climates where huge ambient temperature influences the efficacy of PV systems. This paper examines the use of multi-layered phase change materials (PCMs) in parallel arrangement for PV thermal control to lower the temperature increase and enhance the energy production. The study uses a numerical method to compare and determine the thermal efficiency of PV systems deployed at different angles (0, 30, 45, 75 and 90°) on the PCM's freezing and melting behavior. The usage of multi-layered phase change materials has been demonstrated to effectively reduce the surface temperature of photovoltaic panels by as much as 25 °C, thereby leading to a significant enhancement of electrical efficiency by about 5.18 %. Hence, the study of the liquid fraction contours resulting from the heat transfer operation discloses that a greater tilt angle promotes faster and more effective melting of the PCM. Other maps presenting temperature contours also emphasize that steeper angles result in lower maximum temperatures and small thermal gradients inside the PCM, which are essential to support the required operation conditions.